Implementation of Local Wisdom Based Learning to Enhance Students’ Social Awareness and Learning Culture at UPT SMP Negeri 4 Kelara Jeneponto - Nurhayati Nurhayati; Elpisah Elpisah; Saripuddin Saripuddin; Suarlin Suarlin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to: (1) describe the implementation of local wisdom–based learning in the teaching process of Grade VII B at UPT SMP Negeri 4 Kelara Jeneponto; (2) determine the improvement of students’ social awareness after the implementation of local wisdom–based learning; and (3) identify the enhancement of students’ learning culture through the application of this learning model. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 25 seventh-grade students, focusing on two main variables: social awareness and learning culture. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The findings indicate that the integration of Jeneponto cultural values Tabe’ Karaeng, Sipakatau, Sipakalabbiri, Sipakainga, Siri’ na Pacce, Akbulo Sibatang, and empo sipitangari was implemented effectively and became more optimal in Cycle II after improvements were made through Problem-Based Learning (PBL) and the use of more contextual local cases. Students’ social awareness increased from an average of 63.13% in Cycle I (categorized as Fair) to 80.42% in Cycle II (categorized as High). Similarly, students’ learning culture improved from 69.69% (Fair) in Cycle I to 82.66% (High) in Cycle II, meeting the classical mastery criteria. The study concludes that integrating local wisdom into classroom instruction not only strengthens students’ understanding of social studies content but is also effective in shaping their social character and learning habits. This model is recommended for development in other subjects and educational levels.